Geochemistry of Miocene sedimentary rocks from offshore West Baram Delta, Sarawak Basin, Malaysia, South China Sea: implications for weathering, provenance, tectonic setting, paleoclimate and paleoenvironment of deposition - Ben-Awuah, J. (Korean Association of Geoscience Societies, 2017)
Geochemistry, paleoweathering, provenance, tectonic setting, paleoclimate and paleoenvironment of deposition of offshore Miocene sedimentary rocks in the West Baram Delta have been examined through multi-element geochemistry and mineralogy. Materials and methods used in the study include ninety four core samples from four subsurface wells, XRF, thin sections and FESEM. Four main groups of samples are identified in the wells: porous sandstones, cemented sandstones, siltstones and mudstones. The sandstones are classified as sublitharenites, litharenites and Fe-rich sandstones based on chemical composition and mineralogy. Variations in compositional trends suggest strong lithological and diagenetic controls on the geochemical composition of the samples. Petrography of the samples indicates that they are composed mainly of quartz, K-feldspar, siderite and clay minerals. The samples are characterized by moderate to high degree of chemical weathering with CIA values between 52–76 and PIA values from 65–100. Provenance analysis of the samples shows predominantly felsic and intermediate igneous provenance with minor mafic contribution. The samples are inferred to have originated from a passive margin tectonic setting that followed the continental collision and rifting stages of the foreland basin development phase of the Sarawak Basin. The paleoclimate of deposition of the samples is interpreted to be warm and humid enhancing the chemical weathering. The paleoenvironment of deposition is predominantly suboxic to anoxic. © 2017, The Association of Korean Geoscience Societies and Springer-Verlag Berlin Heidelberg.